2010
DOI: 10.1001/archoto.2010.75
|View full text |Cite
|
Sign up to set email alerts
|

Factors for Maxillary Sinus Volume and Craniofacial Anatomical Features in Adults With Chronic Rhinosinusitis

Abstract: Regardless of CRS, maxillary sinus volume decreased with older age and increased with alveolar bone loss. Regarding craniofacial anatomical features, CRS may have an effect on malocclusion in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 17 publications
(20 reference statements)
2
31
0
Order By: Relevance
“…While maxillary sinuses can develop differently on the two sides, no significant differences were reported when maxillary sinus volumes were compared between the genders and the volumes of each side (3,20). However, Karakas and Kavakli (21) and Uchida et al (22) reported that paranasal sinus volumes differed between genders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While maxillary sinuses can develop differently on the two sides, no significant differences were reported when maxillary sinus volumes were compared between the genders and the volumes of each side (3,20). However, Karakas and Kavakli (21) and Uchida et al (22) reported that paranasal sinus volumes differed between genders.…”
Section: Discussionmentioning
confidence: 99%
“…It is argued that nasal airflow, brain development, muscle strength, and migration play significant roles in their formation (1,2). Volumes of the maxillary sinus and its anatomical neighborhood depend on aeration (3). Maxillary sinus development is directly associated with the alveolar process and hard palate.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation, allergy, gastro-esophageal reflux, current smoking, smoke exposure, septum deviation, inadequate treatment of sinusitis and cilliary dysfunction are all implied in etiology [18]. In a study on adults with CS, Cho et al [7] suggested that maxillary bone wall was thickened as well as sinus volume was reduced in patients with CS. This volume depletion causes increase in convexity of maxillary bone curve and elevation of palatal bone to replace the reduced sinus volume.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a decrease occurs in ciliary action over time; and if the pathology persists for long time, a decrease in the volume of the sinus (silent sinus syndrome) and thickening at wall of sinus become apparent [7]. In this study, we recruited patients with CS, who had a pathology limited to sinus mucosa without septum pathology causing nasal obstruction [8].…”
Section: Introductionmentioning
confidence: 99%
“…Its volume is determined by a number of factors as age, remaining dental pieces, alveolar bone height, etc. (Cho et al 2010), in reference to the presence of chronic sinus pathology, Debb et al (2011) reported a decrease of sinus volume in subjects with chronic rhinosinusitis associated with the increase in thickness of the mucosa and cortical bone.…”
Section: Introductionmentioning
confidence: 99%